Selection, generation and extraction of MCCTree using XMCCTree - Sazaly, Ummu Sulaim; Selamat, Mohd Hasan; Baharom, Salmi; A. Jabar, Marzanah (North Atlantic University Union, 2012)
Previous research proposed notions of CLCA and MCLCA to answer keyword query in XML document. The notions are implemented in its proposed algorithms and the result, namely MCCTree, is ranked with its proposed ranking method. The algorithms transform the XML tree into a compact global tree called CGTree, and select the MCCTree from the CGTree. The resulted MCCTree is in a compact structure; however the calculation in the ranking method requires the original structure as in the XML tree. Thus, this paper presents a new algorithm that implements the same notions with different approach. The MCCTree is returned in a structure as required by the ranking method. This algorithm, called XMCCTree, improve the efficiency of producing a set of MCCTree in answering keyword query in XML document.